DEVELOPMENT STRATEGY OF THE ANDROMEDA TO SUPPORT THE TRAINING OF THE OPERATION CORPS CADETS - Mukhlis Mukhlis; Rakhmad Susilo; Azi Wardiana; Rakam Rakam (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
This research is motivated by the training implementation of the cadet of the operation corps which is not optimal because there are empty rooms in the Andromeda Building do not use optimally. The main objective of determining this strategy is that the empty room in the Andromeda Building can be used optimally. The formulation of the problem from this research is to determine the right strategy in optimizing the Andromeda Room to support cadets of the operation corps. This research is quantitative, this research was conducted by collecting respondents using a questionnaire with a purposive sampling technique. This study uses SWOT analysis, the first step is to create IFAS and EFAS matrices by giving weights to find the total score of the IFAS and EFAS variables. The second step is to formulate a strategy, namely SO, WO, ST, and WT. Further study shows that the advantages of the Andromeda bridge simulator building are designed like the KRI class Sigma. The disadvantage is that the navigation equipment contained in the bridge simulator is not ready in terms of quality or quantity. The results of this study are in the quadrant 3rd position where this condition is to minimize existing internal problems by maximizing existing opportunities through a review strategy to produce something new. Keywords: SWOT Analisis, Andromeda room, Borda Method